Fatty acid metabolism predicts prognosis and NK cell immunosurveillance of acute myeloid leukemia patients - Ye, Zhitao; Li, Yishan; Tian, Xiaobin; Wei, Yan; Yu, Yanhui; Lai, Kaibin; Yang, Keyue; Qiu, Zixuan; Lin, Jianqing; Zhao, Meng; Lin, Dongjun; Xu, Xiaojun (Frontiers in Oncology, 2022)
Background Cell metabolic reprogramming is a hallmark of tumor prognosis, and fatty acid metabolism (FAM) plays a crucial role in the tumor microenvironment (TME). However, the relationship between FAM, TME, and prognosis of acute myeloid leukemia (AML) patients remains elusive. Methods We extracted the single-cell RNA sequencing (scRNA-Seq) and bulk transcriptome data of AML patients from the TCGA and GEO databases and assessed the relationship between FAM, TME, and AML patient prognosis. We also performed functional enrichment (FE) assay to evaluate the significance of FAM in anti-AML immunosurveillance. Results Our scRNA-Seq analysis revealed that the leukemic stem cell (LSC)-enriched population exhibited elevated levels of FAM-related genes. Using these FAM-related genes, we developed a prognostic model that accurately estimated AML patient outcome. FE analysis showed that FAM was strongly related to alterations of TME-based immunosurveillance in AML patients. More importantly, we demonstrated that FAM inhibition via pharmaceutical targeting of PLA2G4A, a highly expressed FAM gene in AML patients with poor prognosis, enhanced the NK cell-mediated immunosurveillance in leukemia cells. Conclusions Leukemic stem cell (LSC)-enriched population exhibited elevated levels of FAM-related genes. We have successfully established the FAM formula that predicts AML patient prognosis and alterations in the TME-based immunosurveillance. We also found that PLA2G4A was a highly expressed FAM gene in AML patients with poor prognoses. Pharmaceutical targeting of PLA2G4A increased the expression of NKG2DL in leukemia cells in vitro and thus enhanced the NK cell-mediated immunosurveillance.